The Ethiopia Strategy Support Program: Example of an impact-focused approach - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
The Ethiopia Strategy Support Program (ESSP), the first major IFPRI country strategy support program managed by the Development Strategy and Governance Division (DSGD), was undertaken in close collaboration with the Ethiopian Development Research Institute (EDRI) from September 2004 through December 2007. The program arose because many complex issues concerning the design, implementation, and monitoring of a pro-poor rural development strategy in Ethiopia remained to be resolved, despite the commitment of government and donors and their articulation of a strategy. Important knowledge gaps related to prioritizing and sequencing activities; targeting investments among regions; determining types of investment and household types to best achieve growth, food security, and poverty reduction; making the rural development strategy actionable; designing feasible instruments for implementation; and monitoring and evaluating the implementation and impact of the rural development strategy.